Die drei Ringe: Entstehung, Wandel und Wirkung der Ringparabel in der europäischen Literatur und Kultur - Aurnhammer, Achim; Cantarutti, Giulia; Vollhardt, Friedrich (Frühe Neuzeit, 2016)
"This volume aims to reconstruct the literary history of the compelling narrative model of the ring parable as a counterweight to contemporary reductionist misinterpretations, and to guide the reader through an archeology of European notions of tolerance. It traces the transformations of the parable from antiquity to Boccaccio, and then goes on to examine Lessing and modern reception."--
Aus der Einleitung: "Der vorliegende Band, der die Ergebnisse eines deutsch-italienischen Forschungskolloquiums vom 27. bis 29. September 2012 in der Villa Vigoni dokumentiert..."
Keywords: Boccaccio, Giovanni -- 1313-1375 -- Decamerone -- Prima giornata, Novella Terza -- Congresses; Lessing, Gotthold Ephraim -- 1729-1781 -- Nathan der Weise -- Congresses; Konferenzschrift -- 2012 -- Menaggio-Loveno; Lessing, Gotthold Ephraim / Ringparabel / Nathan der Weise; Geschichte; Ring; Parabel; Literatur; Europa